Improvement of crane-manipulator equipment for emergency rescue and restoration works - Sukach, Mykhailo; Kravchuk, Anatoliy (Transfer of innovative technologies, 2021)
To implement state policy in the fields of civil protection, protection of the population and territories from emergencies and their prevention, emergency response, rescue, fire fighting, fire and man-made safety, emergency services, as well as hydrometeorological activities There is the State Service of Ukraine for Emergencies (hereinafter SES of Ukraine) [1]. 7 emergency rescue formations (central subordination), including aviation, are subordinated to it; 25 emergency rescue teams of special purpose and 1182 district fire and rescue units (territorial subordination) [2]. According to the main capabilities of the units of the Rescue Service of Civil Defense are divided into: 1) units intended for extinguishing fires, rescuing people and property in case of fires, at facilities and territories, regardless of subordination and form of ownership, conducting emergency rescue operations, providing primary medical care to victims. 2) formation (detachments, centers) designed to eliminate accidents (catastrophes) of technogenic, natural and military nature, the consequences of natural disasters (earthquakes, storms, landslides, landslides, mudslides, floods, snow snowdrifts, icing, etc.), search and rescue, fire and rescue operations, international rescue operations, demining activities and civil and territorial defense measures, national and regional in nature. They include: - fire and rescue units - for firefighting, rescue of people and property at facilities and territories, regardless of subordination and form of ownership. - rescue units - designed to deploy and carry out rescue and other urgent work in the shortest possible time, to search (including the use of service dogs) and rescue people who are in destroyed, burning buildings, under the rubble, including excavation of victims from collapsed buildings, as well as to provide first aid to victims; - engineering - for conducting engineering reconnaissance of routes and centers of destruction, clearing of blockages, excavation of victims from under the damaged constructions, creation of special passages in blockages, collapse of designs, detection of damages in utility and energy and technological networks, preparation and maintenance of roads, formation of fencing anti-fire lanes; - radiation and chemical protection - conduct radiation and chemical reconnaissance, carry out dosimetric and chemical control of units, perform degassing, decontamination of uniforms and other material means, areas, roads and structures; - pyrotechnic - detect and destroy unused ammunition, including aircraft bombs and other explosive devices, neutralize the affected structural elements of buildings and houses, as well as pierce passages in the rubble by explosive methods; --water supply - designed for the development of water sources and equipment of water supply points; - communication - to establish and maintain reliable communication, which provides communication between departments, governing bodies and various forces of interaction; - material support - must timely meet the urgent needs of units with special equipment, fuel, products, protective equipment, clothing, medical, technical property and other material means. Units of the SES of Ukraine have at their disposal a significant amount of equipment, which can be divided, depending on its functionality and purpose for fire and rescue vehicles, vehicles for special work in emergencies and special cars. [3] Of the self-propelled vehicles for emergency response, wheeled vehicles for all types of work have become the most widespread.